The latest diagnostic methods for esophageal and gastric examinations. High-resolution manometry is now available in Ukraine - Yu.M. Stepanov; N.V. Prolom; S.O. Tarabarov (Gastroenterologìa)
To date, there are several advanced methods for diagnosing esophageal and gastric disorders that are actively used in clinical practice, among which high-resolution (HR) manometry stands out. This innovative study provides an opportunity to assess in detail the functional state of the esophagus, in particular the coordination of muscle contractions during swallowing and the function of the lower esophageal sphincter. HR manometry is an effective tool for detecting motility disorders such as achalasia, gastroesophageal reflux disease, diffuse esophageal spasm, as well as other functional disorders that can affect the process of swallowing and moving food through the esophagus. One of the main advantages of HR manometry is accurate diagnosis of functional esophageal disorders due to the use of special catheters with numerous sensors located at a short distance from each other (about 1 cm). This allows you to create detailed topographic maps of pressure in the esophagus, which show the contraction of its muscles in real time. Thanks to this high resolution, it is possible to detect even minor motility disorders that previously went unnoticed when using traditional diagnostic methods. HR manometry has significantly improved the diagnosis of achalasia due to the ability to clearly identify three subtypes of this disease (classic achalasia, pan-esophageal pressure, and spastic achalasia). This allows doctors not only to make a more accurate diagnosis, but also to choose the optimal treatment strategy adapted to the specific type of disorder. In case of gastroesophageal reflux disease, HR manometry helps assess the function of the lower esophageal sphincter and diaphragm, which is important for detecting diaphragmatic weakness, which is one of the main causes of pathological reflux. In addition, this method makes it possible to diagnose concomitant peristalsis disorders that affect the ability of the esophagus to clear from acid reflux, thereby helping doctors better understand the mechanism of the disease and prescribe more effective treatment. Thus, HR manometry has a key place among modern methods for diagnosing esophageal disorders, allowing not only to accurately detect motility disorders, but also to optimize treatment. This significantly improves patients’ quality of life, as it helps doctors choose the most effective therapeutic strategies based on accurate data about esophageal function.